Safety and efficacy of peripheral metaraminol infusion in patients with neurological conditions: a single-center retrospective observational study - Han, Pan; Zhou, Yu (Frontiers in Neurology, 2024)
Introduction Metaraminol is a sympathomimetic amine vasopressor that can be administrated through a peripheral venous access. However, limited evidence restricts its application in critically ill patients. This study aimed to investigate the safety and efficacy of peripheral metaraminol infusion in patients with neurological conditions. Methods Patients who received peripheral metaraminol infusion between May 2019 and April 2022 were recruited. Data on baseline characteristics, clinical parameters, and infusion-related complications were retrospectively collected and analyzed. Results 273 patients who received metaraminol were enrolled. Of these, 35 (12.8%) patients required central venous catheter insertion due to inability in achieving hemodynamic stability following peripheral metaraminol monotherapy. In 29,574.2 hours of vasopressor infusion, metaraminol infusion resulted achievement of the target blood pressure 73.4% of the time. Meanwhile, adverse events occurred in 5 patients and resolved after local tissue treatment. Discussion Metaraminol could provide hemodynamic support and avoid complications associated with a central venous catheter and delay in vasopressor administration. Through careful and close monitoring, peripheral metaraminol infusion is safe and feasible for patients with neurological conditions. Future large-scale, prospective, multicenter studies are needed to evaluate the safety and efficacy of metaraminol infusion through a peripheral intravenous catheter.